2009
DOI: 10.3341/kjo.2009.23.3.188
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Vascular Endothelial Growth Factor After Intracameral Bevacizumab Injection in Eyes With Neovascular Glaucoma

Abstract: PurposeTo study the concentration of vascular endothelial growth factor (VEGF) in the aqueous humor before and after intracameral injection of bevacizumab in eyes with neovascular glaucoma, and to detect the duration of an anti-VEGF effect of bevacizumab in the anterior chamber.MethodsIn this prospective interventional case series, 1.25 mg of bevacizumab was injected into the anterior chamber of five eyes in five neovascular glaucoma patients. Aqueous humor samples were obtained just before intracameral inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 17 publications
1
23
2
1
Order By: Relevance
“…Chalam et al 74 showed complete regression of neovascularization due to aggressive NVG (69% secondary to PDR) within 3 weeks from the treatment with intracameral bevacizumab. Lim et al 75 showed a massive regression of iris neovascularization and a significant reduction in intravitreal VEGF levels in a 2-week period, and no significant changes in IOP in NVG patients treated with intracameral bevacizumab. Eid et al 76 demonstrated that combining PRP with bevacizumab ablated the ischaemic retina and ensured good success rates in patients with intractable glaucoma requiring shunt procedures.…”
Section: Indications Of Anti-vegf Treatment For Pdrmentioning
confidence: 99%
“…Chalam et al 74 showed complete regression of neovascularization due to aggressive NVG (69% secondary to PDR) within 3 weeks from the treatment with intracameral bevacizumab. Lim et al 75 showed a massive regression of iris neovascularization and a significant reduction in intravitreal VEGF levels in a 2-week period, and no significant changes in IOP in NVG patients treated with intracameral bevacizumab. Eid et al 76 demonstrated that combining PRP with bevacizumab ablated the ischaemic retina and ensured good success rates in patients with intractable glaucoma requiring shunt procedures.…”
Section: Indications Of Anti-vegf Treatment For Pdrmentioning
confidence: 99%
“…64 Additionally, a short-term clinical study reported that patients with NVG displayed a considerable reduction in VEGF concentration in the aqueous humor (P=0.04) without a significant change in IOP 2 weeks after receiving an intracameral injection of bevacizumab. 70 In a similar pilot study evaluating the effect of intracameral bevacizumab before any surgical treatment for NVG, some patients were found to no longer require any surgical intervention, whereas other patients became candidates for filtration surgery. 29 Upon testing the use of bevacizumab as a topical treatment, another pilot study found that after topical application of bevacizumab 4 times a day consistently for 2 weeks the mean IOP of eight patients was reduced by 17.5%.…”
Section: Anti-vegf Therapy In Nvgmentioning
confidence: 99%
“…Several studies have reported the safety profile of intravitreal injections of bevacizumab in patients with various retinal pathologies including exudative age-related macular degeneration, central retinal vein occlusion, proliferative diabetic retinopathy, and macular edema, which are associated with upregulation of VEGF production [10][11][12]. Neovascular glaucoma usually develops in eyes with severe ocular ischemia, which causes a marked increase in intraocular VEGF [13][14][15]. Histological and physiological evidence is accumulating that indicates suppression of VEGF by intraocular injection of anti-VEGF agents may cause reduced blood flow in the retina or choroid [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%